2006
DOI: 10.1086/508671
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐Dependent Inhibition Drives Regular Tussock Spacing in a Freshwater Marsh

Abstract: Online enhancements: videos, Matlab code.abstract: Regular spatial patterning is common in nature, and various mechanisms of self-organization have been proposed to explain regular patterning. We report on regular spatial patterning in Carex stricta in a freshwater wetland and investigate the applicability of theoretical models that explain regular patterning based on inhibition, facilitation, or interaction between the two. Spectral analysis of aerial photographs revealed that tussocks were regularly spaced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 26 publications
(57 reference statements)
1
33
0
Order By: Relevance
“…Moreover, the complex physical templates that characterize the real world, for instance in microtopography, can alter both the patterns generated by self-organization processes as well as their emergent effects on ecosystems functioning [19,29]. Hence, beyond making studying self-organized pattern formation using simple models in idealized setting, it is important to understand how these patterns influence ecosystem functioning when set in large-scale, realistic physical environments [25]. For this rsif.royalsocietypublishing.org J. R. Soc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the complex physical templates that characterize the real world, for instance in microtopography, can alter both the patterns generated by self-organization processes as well as their emergent effects on ecosystems functioning [19,29]. Hence, beyond making studying self-organized pattern formation using simple models in idealized setting, it is important to understand how these patterns influence ecosystem functioning when set in large-scale, realistic physical environments [25]. For this rsif.royalsocietypublishing.org J. R. Soc.…”
Section: Discussionmentioning
confidence: 99%
“…We simulated the grid space of 1024 Â 1024 by eight points representing a natural length of 400 Â 400 by 1 m in the real world. The used algorithm was based on an existing two-dimensional model for mussel pattern formation [25] and further extended to allow three-dimensional computations. Starting conditions are homogeneous with a slight spatially variable, random perturbation of mussel biomass, in order to mimic the initial settlement of young mussels on the sediment surface.…”
Section: Model Analysesmentioning
confidence: 99%
“…Cordgrass modifies water flow and increases the deposition of sediments and the accumulation of peat substrate (Redfield 1972). Through this building process and scale-dependent interactions between vegetation growth, substrate building, and water flow, the developing marsh vegetation can generate hummocks (Bouma et al , 2009van de Koppel & Crain 2006), elevation gradients, and other landscape features (van de Koppel et al 2005b), which contrasts with the previous assumption that vegetation zonation is simply a product of elevation gradients (and associated local variations in abiotic and biotic drivers). Over time, however, this process can lead to the marsh being overbuilt-for example, facilitative interactions can stimulate local sediment buildup, increasing the height of the marsh.…”
Section: Cordgrass and Forbs On Cobble Beaches And In Salt Marshesmentioning
confidence: 97%
“…Yet an upper zone of wave-vulnerable forbs is often present behind lower beds of cordgrass (Spartina alterniflora) that absorb wave energy (Bruno 2000). Experiments have revealed that this vertical zonation pattern is the product of scale-dependent interactions, including competition between the cordgrass and the forbs at short distances on the one hand and longer-distance facilitation on the other (van de Koppel et al 2006) (Figure 1). It was found that the baffling of waves by cordgrass facilitated forb growth behind the cordgrass beds while competition for light suppressed forb growth within the cordgrass beds; mowing of vegetation at the upper edge of the cordgrass stands led to the immediate emergence of forb species.…”
Section: Cordgrass and Forbs On Cobble Beaches And In Salt Marshesmentioning
confidence: 99%
See 1 more Smart Citation